2011
DOI: 10.1016/j.polymer.2011.10.055
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of fiber curvature to the elastic moduli of electrospun nonwoven fiber meshes

Abstract: Adequate mechanical integrity of nonwoven fabrics is generally a prerequisite for their practical usage. Nonwoven fiber mats of poly(trimethyl hexamethylene terephthalamide) (PA 6(3)T) with average fiber diameters from 0.1 to 3.6 microns were electrospun from solutions in dimethylformamide and formic acid and their in-plane mechanical response characterized. Two quantitative microstructure-based models that relate the Young's moduli of these fabrics to those of the fibers are considered, one assuming straight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 21 publications
4
64
0
1
Order By: Relevance
“…However, the number and dimensions of pores, decreases in the following order, 15 % PLA > s-MWCNTs > l-MWCNTs ( figure 9). It has been reported previously that the Young's modulus in nonwoven fabrics is affected by porosity, fiber diameter, radius of curvature, and the distance between the junctions where fibers cross [21]. Therefore, not a single factor is responsible for the mechanical properties, but we can see a trend in our results that smaller fiber composition, together with bigger pores seems to somewhat enhance the Young's modulus.…”
Section: Mechanical Propertiessupporting
confidence: 62%
“…However, the number and dimensions of pores, decreases in the following order, 15 % PLA > s-MWCNTs > l-MWCNTs ( figure 9). It has been reported previously that the Young's modulus in nonwoven fabrics is affected by porosity, fiber diameter, radius of curvature, and the distance between the junctions where fibers cross [21]. Therefore, not a single factor is responsible for the mechanical properties, but we can see a trend in our results that smaller fiber composition, together with bigger pores seems to somewhat enhance the Young's modulus.…”
Section: Mechanical Propertiessupporting
confidence: 62%
“…The influence of the scaffolds and its material parameters (fiber diameter, curvature and orientation; material flexibility and rigidity, etc.) and how they affect the mechanical response, was investigated before (Rizvi et al, 2012;Pai et al, 2011). As in random nanofibrous materials, not all the fibers are in the load-bearing direction, the response would depend on how many fibers are recruited and aligned during the tensile test.…”
Section: Uniaxial Tensile Testsmentioning
confidence: 99%
“…For some applications such as tissue engineering, where a soft, porous matrix is desirable, this may be an advantage; however, for many applications of nonwoven mats, notably membranes and textiles, for example, modest improvements to the mechanical integrity without significant losses in the inherently high porosity or specific surface area would be highly desirable. Although many experimental studies have been conducted on the mechanical properties of conventional nonwoven fabrics, there are a limited number of reports that account adequately for the observed mechanical properties of mats comprising electrospun fibers [14,15]. In recent years several research groups have demonstrated significant improvements to the Young's modulus and yield stress of electrospun polymeric fiber mats by various forms of post-spinning techniques such as thermal annealing [16,17], mechanical drawing [18], hot pressing [19], and solvent vapor treatment [20].…”
Section: Introductionmentioning
confidence: 99%